Lessons for green management from the Hispanic Civil Rights movement: a pseudo-gap analysis. Issue 2 (17th February 2021) - Pane Haden, Stephanie; Randolph-Seng, Brandon; Hasan, Md. Kamrul; Williams, Alex; Hayek, Mario
Abstract : Purpose: Although green management has gained legitimacy as a sustainable business practice, little is known about the elements that will lead to the long-term success of the movement. To identify these elements, this study aims to review the existing literature on social movements and analyzes archival data from a specific social undertaking, the Hispanic Civil Rights movement in the USA. Design/methodology/approach: A historiographical approach was used in which systematic combining used abductive logic to developed a provisional framework based on the interpretation of secondary sources of data concerning the Hispanic Civil Rights movement. Subsequently, an ethnomethodologically informed interpretation of primary data based on the League of United Latin American Citizens (LULAC) archives refined the provisional framework. Findings: The authors identified common elements that are critical to the success of social movements, as supported by both secondary data on the Hispanic Civil Rights movement and primary data based on the LULAC archives. These elements consist of: ideology, identity, mobilization, goals, leadership and integration. Using these results, a pseudo-gap analysis approach was completed by systematically comparing the interpretive data with current knowledge of the green management movement to identify the missing gaps and to offer guidance for further development of green management as a contemporary movement. Social implications: Applying the lessons learned from social movements will help the development and prosperity of the green movement in current business organizations. Such applications are important, given that local and global environmental crises can have profound implications on ecosystems, economics and social systems. Originality/value: Social movements are an important means by which societal concerns such as injustices are addressed. By identifying the important elements needed for the green management movement to be successful in the long term, managers will know where to put their efforts. Such actions may help environmental awareness in business organizations to become more than a fad or marketing tool.